Children’s use of Spanish taps: A naturalistic study with monolingual Costa Rican children ages 3;0 to 5;6 - Vásquez Carranza, Luz Marina (2014)
This study reports on the trends in children’s use of taps by 15 Costa Rican Spanish-speaking monolingual children between ages 3;0 and 5;6. Data were obtained through audio-recordings of the children’s naturalistic speech, yielding 1080 target-words. 80% of the taps were correct, but the remaining 20% evidenced either omissions of the tap (14%) or substitution of the tap for [l], [n], [t], [d], [j], [tS], [D], or for a voiceless assibilated rhotic. A main finding in this study was the consistent omission of the tap in infinitive verb forms before a consonant initial enclitic pronoun. This omission type is interesting in that it appears to be directly related to the complexity involved in nominal enclitics, as children do not always omit the tap in similar phonetic contexts (i.e., /Cr/ clusters). Although this last pattern has been reported for adult Costa Rican Spanish, it has never been reported in child speech.